2020
DOI: 10.1016/j.ibror.2020.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Expression of huntingtin-associated protein 1 in adult mouse dorsal root ganglia and its neurochemical characterization in reference to sensory neuron subpopulations

Abstract: Highlights This study is the first to examine HAP1-expression in dorsal root ganglia (DRG). HAP1 is highly co-expressed with the markers of nociceptive/proprioceptive neurons. HAP1 is completely lacking in the touch-sensitive DRG neurons. HAP1 may play an important role in modulating nociceptive/proprioceptive functions. It will be of great interest to clarify the pathophysiological role of HAP1 in DRG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 92 publications
1
9
0
Order By: Relevance
“…Thus, many nociceptive signal transduction pathways are connected to HAP1 function. In addition, in a completely different approach, the authors of a recent immunolabeling study showed an important overlap between HAP1 and different neurochemical markers in the mouse dorsal root ganglion (DRG) neurons and suggested a role for HAP1 in pain transduction ( Islam et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, many nociceptive signal transduction pathways are connected to HAP1 function. In addition, in a completely different approach, the authors of a recent immunolabeling study showed an important overlap between HAP1 and different neurochemical markers in the mouse dorsal root ganglion (DRG) neurons and suggested a role for HAP1 in pain transduction ( Islam et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of visceral sensitivity is attributed to both central and peripheral CGRP release [ 39 – 41 ]. In the process of pain conduction in the spinal cord, neuropeptides, such as CGRP and SP, released at the central end of the primary afferent nerve fibers, contribute to the depolarization of neurons in the superficial layer of the posterior foot of the spinal cord [ 42 ]. The increased expression of c-fos during pain reflects the partial adaptive response of the spinal cord to continuous and subsequent nociceptive inputs [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Details for the methodology of immunohistochemistry were described in our earlier studies [ 43 , 46 ]. In brief, pre-incubation of the sections was done with PBS containing 10% normal goat serum (NGS) and 0.3% Triton X-100 at 4 °C for 60 min.…”
Section: Methodsmentioning
confidence: 99%